The Italian water movement and the politics of the commons - Chiara Carrozza; Emanuele Fantini (Water Alternatives, 2016)
The article contributes to the debate on the commons as a political strategy to counter the privatisation of water services by focusing on the experience of the Italian water movement. It addresses the question: how has the notion of the commons – popularly associated with the Global South – been understood, adopted and translated into practice by social movements in a European country like Italy? We identify three different understandings of the commons coexisting within the Italian water movement – emphasising universality, locality and participation. We describe the political claims and the initiatives informed by these understandings, and the actors which promoted them. Our analysis underlines that the polysemy of the notion of the commons, its complementarity with the 'human right to water' and its overlapping with the idea of 'public' not only proved to be effective in the Italian case, but also posed challenges when it came to translate the notion of the commons into specific governance and management frameworks. The politics of the commons defines the space where these dynamics unfold: it is more articulated than a mere rhetorical reference to the commons, but less homogeneous and coherent than the idea of a 'commons movement'.